Bolstering family control: Evidence from loyalty shares - Bajo, Emanuele; Barbi, Massimiliano; Bigelli, Marco; Croci, Ettore (Journal of Corporate Finance, 2020)
We study the introduction of a new control-enhancing mechanism in Italy, a country still characterized by family-controlled firms but with an increasing importance of institutional investors. Since 2014, Italian firms have been able to adopt loyalty shares, which allow a double voting right if shares are continuously held for at least two years. We find that about 20% of listed firms have introduced loyalty shares, and family-controlled firms are the most likely adopters. Loyalty shares neither anticipate acquisitions, nor equity issues by the adopting firm. Instead, they allow controlling shareholders to reduce their equity stake without losing control. We report no evidence of an adverse wealth effect both at the adoption and in the years following it. As expected, institutional investors vote against the introduction of loyalty shares. Yet, they do not reduce their holdings afterwards, as incremental governance costs are outweighed by the superior performance of adopting firms. Overall, our evidence suggests that bolstering family control is the main effect of the introduction of loyalty shares.